Correction to: Training During the Covid-19 Lockdown: Knowledge, Beliefs, and Practices of 12,526 Athletes from 142 Countries and Six Continents (Sports Medicine, 2022 52 4 (933-948), 10.1007/S40279-021-01573-Z) - Herrera-Valenzuela, T (Springer Science and Business Media Deutschland GmbH, 2022)
The affiliation of the author Lone Bogwasi, which previously read as: Lone Bogwasi Department of Orthopedics, Nyangabgwe Hospital, Francistown, Botswana Botswana Football Association Medical Committee, Gaborone, Botswana. © The Author(s) 2022.